Making Fermented Feed to Trigger the Growth of Seawater Lobsters in the Pasir Putih Group, Ekas Buana Village, Jerowaru District, East Lombok Regency, West Nusa Tenggara - Pratama, Gede Agus; Suryani, Sang Ayu Made Putri; Sumsanto, Muhammad; Kawan, I Made; Darmadi, Ni Made; Sudiarta, Gede; Sudiarta, Ketut; Parawangsa, Nyoman Yoga; Edi, Dewa Gede Semara (Indonesian Journal of Society Development, 2024)
The aim of this community service is to improve the knowledge, skills and attitudes of cultivators, especially lobster cultivators. Training and counseling is carried out directly in the field, with material first provided, practice carried out, and the discussion concluded. The venue for the event was Ekas Buana Village in Jerowaru District, East Lombok Regency, West Nusa Tenggara Province. The first step in making fermented feed is to determine the feed formulation, weigh the feed, and then mix the starting feed with the smallest amount of feed ingredients. Followed by fermentation and steaming of the feed. The feed produced from this fermentation can be used to feed lobsters, especially in musism where trash feed and squid or natural feed are difficult to find